EXCELLENCE/0524/0001 - Costa, Marios (My University, 2026)
Strong Interactions on a spacetime Lattice: Quantum Chromodynamics and its Supersymmetric version Funding from the Research and Innovation Foundation of Cyprus – €200,000. I was the original Project Coordinator of the StrongILA project securing the funding (contract number EXCELLENCE/0524/0001), with the Host Organization being the University of Cyprus and the Partner Organization being Rinnoco Ltd. However, due to my appointment as Special Teaching Staff at the Cyprus University of Technology, I had to step down as Project Coordinator and appointed Dr. Gregoris Spanoudes as my successor.
Keywords: Sciences